Design and Experimental Verification of a Bidirectional EV On-Board Charger Featuring Multiphase Operation in Full Power/Voltage Ranges - Hector Sarnago; Oscar Lucia (IEEE Open Journal of the Industrial Electronics Society)
Modern electric vehicles require power electronic systems capable of operating under a wide variety of operating conditions, including on-board chargers (OBCs) and dc–dc converters. These systems must function across a wide range of parameters, such as phase number, input voltage, and output battery voltage. Considering modern design standards, achieving a high-performance implementation featuring high efficiency and low cost is also mandatory, adding additional technical challenges. To address these challenges, this article proposes a novel OBC architecture designed to operate in both three-phase and single-phase configurations across the full output power range. This is achieved without requiring additional power components or degrading performance. As a consequence, the proposed solution is a universal-charging single-power-processing block that features a cost-effective implementation while achieving high power density and efficiency. In this article, a bidirectional 11-kW 800-V-battery-voltage prototype of the system is designed and constructed for a 400-V (line-to-line) mains supply.